Pannexin 3 is required for normal progression of skeletal development in vertebrates. Issue 11 (16th July 2015) - Oh, Se‐Kyung; Shin, Jeong‐Oh; Baek, Jeong‐In; Lee, Jinwook; Bae, Jae Woong; Ankamerddy, Harinarayana; Kim, Myoung‐Jin; Huh, Tae‐Lin; Ryoo, Zae‐Young; Kim, Un‐Kyung; Bok, Jinwoong; Lee, Kyu‐Yup
ABSTRACT: The vertebrate skeletal system has various functions, including support, movement, protection, and the production of blood cells. The development of cartilage and bones, the core components of the skeletal system, is mediated by systematic inter‐ and intracellular communication among multiple signaling pathways in differentiating progenitors and the surrounding tissues. Recently, Pannexin (Panx) 3 has been shown to play important roles in bone development in vitro by mediating multiple signaling pathways, although its roles in vivo have not been explored. In this study, we generated and analyzed Panx3 knockout mice and examined the skeletal phenotypes of panx3 morphant zebrafish. Panx3 ‐/‐ embryos exhibited delays in hypertrophic chondrocyte differentiation and osteoblast differentiation as well as the initiation of mineralization, resulting in shortened long bones in adulthood. The abnormal progression of hypertrophic chondrogenesis appeared to be associated with the sustained proliferation of chondrocytes, which resulted from increased intracellular cAMP levels. Similarly, osteoblast differentiation and mineralization were delayed in panx3 morphant zebrafish. Taken together, our results provide evidence of the crucial roles of Panx3 in vertebrate skeletal development in vivo .—Oh, S.‐K., Shin, J.‐O., Baek, J.‐I., Lee, J., Bae, J. W., Ankamerddy, H., Kim, M.‐J., Huh, T.‐L., Ryoo, Z.‐Y., Kim, U.‐K., Bok, J., Lee, K.‐Y. Pannexin 3 is required for normal progression of skeletal development in vertebrates. FASEB J. 29, 4473‐4484 (2015). www.fasebj.org